Pengaruh Kelas Sosial Karl Marx terhadap Akses Pendidikan Bahasa Jepang di Program Studi Pendidikan Bahasa Jepang Universitas Negeri Jakarta - Sulaiman Syam, Muhammad Ali; Amelya Septiana, Amelya (Universitas Negeri Jakarta, 2025)
This study analyzes the influence of social class on access to Japanese language education in the Japanese Language Education Program at Universitas Negeri Jakarta, using Karl Marx's social class theory as a framework. The study aims to identify disparities in educational access experienced by students based on their socio-economic backgrounds. A quantitative field research approach was adopted, involving all students of Class B, Batch 2024, as respondents. Data were collected through questionnaires measuring family income, access to educational resources, and learning experiences. The findings reveal that students from low-income families often face difficulties purchasing textbooks, rarely attend additional courses, and underutilize learning facilities. In contrast, students from higher-income groups have better access to educational resources. These results affirm that socio-economic disparities significantly influence educational access, necessitating